Agreement between initial and final diagnosis of first seizures, epilepsy and non-epileptic events: a prospective study. Issue 10 (12th February 2008) - Leung, H; Man, C Y; Hui, A C F; Wong, K S; Kwan, P
Abstract : Background: Differentiating between first seizure, epilepsy and a non-epileptic event is a challenging clinical exercise for many physicians as it may lead to different therapeutic implications. This study aims to investigate the agreement between the initial diagnosis at the accident and emergency (A&E) department and the final diagnosis following inpatient neurological evaluation of seizure disorders. Method: A prospective observational study between April 2004 and June 2005 in a regional hospital in Hong Kong recruited 1701 patients from the A&E to neurology/medical wards with initial diagnoses/labels matching any one of 12 predefined keywords which were categorised as either "seizure specific" or "non-specific". Results: Among the 1170 patients with "non-specific" initial diagnoses/labels, 58 (5%) were finally diagnosed as having had a first seizure or epilepsy. Among 531 patients with "seizure specific" initial diagnoses/labels, 27 (5.1%) were subsequently diagnosed as having had non-epileptic events. The κ value for agreement between the initial and final diagnosis was 0.88. Of the 154 patients with a final diagnosis of first seizure, 34 (22%) had "non-specific" initial labels. Among these patients, components of the evaluation contributing to revision of diagnosis included retrieval of witness accounts (47%), epileptiform discharges on EEG (47%), short term monitoring in patients suspected of acute symptomatic seizures (28%) and panel discussion of cases (22%). Conclusion: There was generally a high degree of agreement between the initial and final diagnosis, but first seizures were often missed initially. Careful history taking, judicious use of EEG, selective short term monitoring and liaison with specialists are important in reaching an accurate diagnosis.